Eit industrisamfunn ser tilbake - Ågotnes, Hans-Jakob (Tidsskrift for kulturforskning, 2007)
This article explores the changing conceptions of an industrial community at a time when industry is about to be viewed as a phenomenon of the past. The history of the place, its landscape and its relations to the surrounding district are affected when people, activated by a newly-built museum, become engaged in re-evaluating their past. In the process, various material structures of the place are invested with new meanings, thereby becoming monuments over the local industrial history. But in the creation of this meaning, oral storytelling (in increasing degree supplemented by mediation in written form) play a vital role. A local version of the past emerges, but in a manner that places the community in a relationship both to the surrounding district and to the national dimension. As such, the elaboration of the past contributes to the identity work of this local community.